Strategic Management - Greenley Gordon E (Prentice Hall, 1989)
This book is highly illustrated with case studies and company illustrations to show the application of strategic management concepts to real European companies. Preface, Introducing Strategic Management, The Nature of Strategic Management, The Integrative Case Study, Analyzing the Environment, Strategic Audits, Understanding Competitors, Understanding Market Structures, Planning Direction, Organizational Mission, Organizational Objectives, Values and Expectations, Planning Strategy, Structural Influences, Strategy Alternatives, Strategy Selection, Implementing Strategy, Operational Strategies, Human Resource Management, Control and Effectiveness, Name and Subject Index.